Acute effects of aerobic running on blood pressure In young normotens adults - Wollner Materko; Alex Lima Brito; Dilson Rodrigues Belfort (Revista da Educação Física)
The aim of the present study was to investigate the acute effects of blood pressure induced by moderate intensity aerobic exercise in young adults. Thirty-one individuals (18 women and 13 men) were submitted an anthropometric evaluation and a 40-min running protocol between 60% and 70% of the reserve heart rate. Hemodynamic measurements, systolic blood pressure (SBP) and diastolic blood pressure (DBP) were carried out before and after the running protocol through Student's t-test for the dependent variables. All tests assumed α = 0.05. Significant differences were recorded between SBP before (127.1 ± 11.5 mmHg) and after (119.9 ± 10.2 mmHg) the running protocol. The results showed a decrease in systolic blood pressure, which resulted in a mean difference of -7.2 ± 6.2 mmHg, demonstrating a significant difference (p = 0.00001). However, in the DBP before (73.6 ± 8.6 mmHg) and after (72.5 ± 7.8 mmHg) no showing a significant difference (p = 0.36) as an acute effect on the decrease the running protocol. In conclusion, that moderate intensity and long duration running exercise can be aided in the non-pharmacological treatment of arterial hypertension and as an improvement in cardiovascular health.